2017
DOI: 10.5812/archneurosci.44254
|View full text |Cite
|
Sign up to set email alerts
|

A mouse Model of Focal Vascular Injury Induces Astrocyte Reactivity, Tau Oligomers, and Aberrant Behavior

Abstract: Neuropsychiatric symptom development has become more prevalent with 270,000 blast exposures occurring in the past 10 years in the United States. How blast injury leads to neuropsychiatric symptomology is currently unknown. Preclinical models of blast-induced traumatic brain injury have been used to demonstrate blood-brain barrier disruption, degenerative pathophysiology, and behavioral deficits. Vascular injury is a primary effect of neurotrauma that can trigger secondary injury cascades and neurodegeneration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…These data from App -KI mice suggest that anxiolytic-like behaviors observed in mouse models of Aβ amyloidosis are associated with Aβ-mediated pathologies [ 24 , 53 ] rather than overexpression of APP. Interestingly, some mouse models with traumatic brain injury exhibit increases in open arm exploration in the EPM task, followed by elevated levels of reactive gliosis and cerebrovascular dysfunction [ 63 66 ]. Another study demonstrated that local neuroinflammation within the dorsal raphe nucleus, resulting in serotonergic hypofunction, caused the same behavioral consequences in the EPM task [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data from App -KI mice suggest that anxiolytic-like behaviors observed in mouse models of Aβ amyloidosis are associated with Aβ-mediated pathologies [ 24 , 53 ] rather than overexpression of APP. Interestingly, some mouse models with traumatic brain injury exhibit increases in open arm exploration in the EPM task, followed by elevated levels of reactive gliosis and cerebrovascular dysfunction [ 63 66 ]. Another study demonstrated that local neuroinflammation within the dorsal raphe nucleus, resulting in serotonergic hypofunction, caused the same behavioral consequences in the EPM task [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mice, from which the brains were obtained, were 6-month-old wild-type C57BL/6 male mice that had undergone blast-induced traumatic brain injury (mTBI) as described in Fig. 1 (Logsdon et al , 2017). The mice were placed in a PVC pipe with the head extending from one side.…”
Section: Methodsmentioning
confidence: 99%
“…In our well-established and characterized battlefieldrelevant rat model of blast-induced mTBI, we found that animals exhibited increased levels of immunoreactive p-tau following blast exposure in the anterior cingulate and anterior motor/sensory cortices. Prior studies have addressed tau processing in experimental animal models of blast TBI, with many reporting elevated levels of tau in brain or blood [21,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. Two studies reported the presence of tau oligomers following blast exposure [59,61] and others have suggested that p-tau metabolism following blast may be regulated by APOE genotype [62].…”
Section: Discussionmentioning
confidence: 99%